Subjective Assessment by Patients of the Efficiency of Two Denture Adhesive Pastes - Yasemin Kulak, PhD;1 Mutlu ¨Ozcan, PhD, DMD;2 and Ayla Arikan, PhD1 (Journal of Prosthodontics, 2005)
This study evaluated the subjective responses of 30 denture wearers with regard to the effectiveness of two denture adhesive pastes.